Hemispheric Security and the National Intelligence Culture Conundrum in Small States: The Case of Guyana - Nte, Ngboawaji Daniel; Featherstone, Clairmont Roger (Razón Crítica, 2026)
More often than not, small states are usually surrounded by large predatory states that hinder their sustainable development trajectory. Although many small states—such as Qatar, Oman, Switzerland, and Singapore—have successfully navigated these difficult socio-political conditions and have emerged as substantially strong and virile nations, there are many others that face diverse latent and real intelligence and national security threats that lurk around them, which have arisen from both historical and geostrategic inadequacies. Consequently, this study evaluates the impregnable challenges of crafting a dependable national intelligence and geostrategic culture in Guyana—a small state nestled in the north-eastern corner of South America—based on hemispheric security model. Indeed, the findings of the study show that historical, social and political factors have greatly impacted the capacity of Guyana’s government to craft a sustainable national intelligence and a geostrategic culture in the country. As a matter of fact, factors as the postcolonial hangover, political admixtures, and sentimental politics (race and ethnic) have all accentuated the impact of the external hostile geopolitical environment in stifling Guyana’s national security. This situation has been magnified in the last few years by the oil boom and the unprecedented economic development of the small Caribbean state. This context also reveals that a potential regional implosion is underway due to the struggle for Guyana’s wealth by internal and external interests that have dire security challenges. Finally, the article underscores that a pragmatic nationalistic nation building efforts is necessary to prioritize the development of an actionable national intelligence and a security culture as a way out of this conundrum.